2022
DOI: 10.1097/j.pain.0000000000002635
|View full text |Cite
|
Sign up to set email alerts
|

Transient receptor potential melastatin 8 is required for nitroglycerin- and calcitonin gene-related peptide–induced migraine-like pain behaviors in mice

Abstract: Mice lacking transient receptor potential melastatin 8 channels or neurons, or treated with a transient receptor potential melastatin 8–specific antagonist, are insensitive to known inducers of migraine-like pain, demonstrating that this cold-gated channel mediates migraine pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Both drugs were delivered through intraperitoneal route in all experiments. NTG-induced acute migraine model with a dose of 10 mg/kg is already extensively validated by many studies [ 8 , 27 – 29 ], therefore, we adopted the same dose for our study. For LVC-induced acute migraine model, we administered 1 mg/kg LVC, a dose used in an LVC-induced chronic migraine model [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Both drugs were delivered through intraperitoneal route in all experiments. NTG-induced acute migraine model with a dose of 10 mg/kg is already extensively validated by many studies [ 8 , 27 – 29 ], therefore, we adopted the same dose for our study. For LVC-induced acute migraine model, we administered 1 mg/kg LVC, a dose used in an LVC-induced chronic migraine model [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…A recent study using transgenic knockout TRPM8 mice suggests a protective role in promoting a faster recovery from chronic migraine-like symptoms in male mice compared to that in female mice [126]. However, another study with transgenic mice showed that TRPM8 channels or afferents are both required for the development of acute and chronic migrainelike symptoms [127]. This suggests that further investigations are needed to determine the role and therapeutic potential of TRPM8.…”
Section: Trp Channels As Targets For Anti-migraine Drugsmentioning
confidence: 99%
“…A recent study using transgenic knockout TRPM8 mice suggests a protective role in promoting a faster recovery from chronic migraine-like symptoms in male mice compared to that in female mice [115]. However, another study with transgenic mice showed that TRPM8 channels or afferents are both required for the development of acute and chronic migraine-like symptoms [116]. This suggests that further investigations are needed to determine the role and therapeutic potential of TRPM8.…”
Section: Trpm8mentioning
confidence: 99%